Analysing Pan Evaporation to Understand Wastewater Treatment Plant Performance, A Case Study in A Manufacturing Industry - Rifai, Ridwan Muhamad; Rahmadhani, Fikri Iqbal; Saputro, Endro Hargi; Sarda Dewi, Mega Septia; Pasaribu, Aswin (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Water loss has become a problem with the balance of a water system, including one in the industry. General opinion has considered evaporation as one of the main justifications for explaining the water loss, especially in the area with a higher daily temperature. A study was conducted on a wastewater treatment system owned by a manufacturing industry consisting of semi-open-air sedimentation and aeration ponds, which suddenly experienced a significant deficit in its water balance. Problem-solving was performed by 8-Step Problem Solving approach and root causes were confirmed by estimating water evaporation. The actual water evaporation rate (E) was approached by pan evaporation (Epan) using the partial pressure of the water vapour and the pan evaporation coefficient (Kpan). The study revealed that evaporation (1.670.59mm.d-1 and 1.720.62mm.d-1, for sedimentation pond and aeration pond, respectively) was not the main cause of sudden significant water loss (R2 = .490, p-value .05) and confirmed another root cause. In parallel, a water balance model was constructed and fitted the actual condition (R = .987). A countermeasure was performed against the confirmed root cause followed by a monthly evaluation of water loss using the constructed model with a 3 threshold value (UCL = 9.55%) which showed the elimination of the problem.